The Effect of Sex on the Chemical and Mineral Composition of the Meat, Bone and Liver of Giraffe (Giraffa giraffa angolensis) - Hoffman, Louwrens Christiaan; Silberbauer, Bianca L; Needham, Tersia; Bureš, Daniel; Kotrba, Radim; Strydom, Philip E (Foods (Basel, Switzerland), 2024)
Consumers tend to buy meat based on visual physical characteristics, which are affected by the chemical composition of the meat, and there is very little known about the chemical composition of the meat of giraffe. This study therefore aims to broaden the knowledge base on the chemical composition of giraffe meat, rib bone and liver. Eight different muscles from 15 giraffes were analyzed to determine the chemical composition, yielding an average moisture of 77.2 ± 0.09 g/100 g meat, an average protein of 20.8 ± 0.09 g/100 g meat, an average intramuscular fat (IMF) of 1.4 ± 0.03 g/100 g meat and an average ash of 1.1 ± 0.01 g/100 g meat. There was a significant interaction between sex and muscle for the moisture, protein and ash contents, while only muscle had an effect on the fat content. The mineral content of the bone, liver and Longissimus thoracis et lumborum muscle was also analyzed, and bone was found to be a rich source of calcium (highest concentration), whilst the liver had the highest concentration of iron. The chemical composition of the giraffe meat was such that it could be classified as lean meat.
Keywords: mineral; bone; muscle; giraffe; protein; moisture; game meat; ash; lipid content; liver